2017
DOI: 10.1089/pop.2016.0197
|View full text |Cite
|
Sign up to set email alerts
|

Qualifications and Competencies for Population Health Management Positions: A Content Analysis of Job Postings

Abstract: The need for population health management expertise has increased as the health care industry shifts toward value-based care. However, many organizations report hiring gaps as they seek to fill positions. The purpose of this study was to analyze the types of population health management positions for which health care organizations are hiring, including qualifications and competencies required for these positions. A content analysis was conducted on 271 job postings collected during a 2-month period. A typolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
1
10
0
2
Order By: Relevance
“…This is not common practice, however: Rotem et al found commonalities in competencies expressed, such as “communication skills” and “interpersonal activity capabilities” 4 . Similarly, a content analysis of public health management positions found a high listing of competencies relating to communication, leadership, management and coordination 28 . We did not think that our current study would have been enriched by such an analysis.…”
Section: Implications For Public Healthmentioning
confidence: 67%
“…This is not common practice, however: Rotem et al found commonalities in competencies expressed, such as “communication skills” and “interpersonal activity capabilities” 4 . Similarly, a content analysis of public health management positions found a high listing of competencies relating to communication, leadership, management and coordination 28 . We did not think that our current study would have been enriched by such an analysis.…”
Section: Implications For Public Healthmentioning
confidence: 67%
“…Concerning culture, participants called for culture change ( 24 , 31 , 47 , 56 ) and mentioned the need for specific cultures, particularly cultures that are transparent and blame-free ( 14 , 31 , 48 , 53 , 56 , 66 , 69 , 72 ). Related to HR and capacity, studies discussed staffing constraints ( 33 , 49 , 59 , 61 ), the importance of staff stability ( 24 , 59 , 66 ), staff composition including the use of alternative providers and medical assistants [e.g., ( 14 , 24 , 33 , 35 , 60 , 64 66 , 71 , 72 , 76 )] and specific open job positions ( 33 , 34 , 62 , 72 , 78 ). Remarks made about organizational facilities and approaches involved professionals' desire for dedicated VBHC time ( 14 , 59 , 66 ), step-by-step implementation ( 34 , 35 , 56 , 72 , 76 ), and an overall supportive environment ( 24 , 31 , 53 , 54 , 56 , 57 , 59 , 62 , 65 , 66 , 72 , 73 ) with specific attention for engaged leadership ( 14 , 33 , 35 , …”
Section: Resultsmentioning
confidence: 99%
“…Ojekalu et al [66] declare that healthcare quality can be improved by supportive visionary leadership; proper planning; education/training; availability of resources; effective management of resources, employees, and processes; and collaboration/cooperation between providers. For Meyer [67], healthcare organizations are invested in improving services, mainly combining operational, improvement, and program managerial expertise. For Dias et al [68], lean philosophy is one of the strategies that focuses on quality improvement and cost reduction.…”
Section: Competencies For Healthcare Professionalsmentioning
confidence: 99%
“…Donating [32] Engaging with clinical partners [32] Engaging in the culture and environment [40] Experiencing all shifts [32] Experiencing hospital services [32] Financial management [24] Governance and leadership [28] Human resource management [28] Improving services [67] Influencing skill [55,56] Innovation [55,56,66,81,82] Leadership [21,24,26,30,31,33,34,[36][37][38][39][40][41][42][43][49][50][51][52]66,81,82] Managing and making change [34] Managing services [28,34] Organization [31,35,36,48] Performance management and accountability [28] Political analysis and dialogue [28] Political and legal issues …”
Section: Competency Authormentioning
confidence: 99%